Exercise-induced asthma in figure skaters - Mannix, E. T.; Farber, M. O.; Palange, P.; Galassetti, P.; Manfredi, F. (Chest, 1996)
Many highly trained athletes experience exercise-induced bronchospasm (EIB): studies describing EIB in figure skaters, who may be at increased risk of EIB due to rink temperatures (7 to 10 degrees C), have not been published. We studied professionally coached figure skaters (n = 124) for EIB by spirometry at rinkside immediately before a simulated long program and at 0 to 1, 5, 10, and 15 min postexercise. Postexercise spirometry revealed the presence of EIB (a decrease from baseline in FEV1 of at least 10%) in 43 skaters, while the remainder (n = 81, control group) remained relatively stable. Pre-exercise FEV1, FVC, and FEV1/FVC ratio were not different between groups. The EIB group had significantly lower FEV1 vs baseline at each measurement following exercise: baseline, 3.08 +/- 0.13; 0 to 1 min postexercise, 2.81 +/- 0.13 (p < 0.05); 5 min postexercise, 2.77 +/- 0.14 (p < 0.05); 10 min postexercise, 2.78 +/- 0.13 (p < 0.05); 15 min postexercise, 2.78 +/- 0.13 (p < 0.05). The EIB group also had lower FVC: baseline, 3.48 +/- 0.16; 0 to 1 min postexercise, 3.16 +/- 0.15 (p < 0.05); 5 min postexercise, 3.19 +/- 0.15 (p < 0.05); 10 min postexercise, 3.27 +/- 0.16 (p < 0.05); 15 min postexercise, 3.26 +/- 0.16 (p < 0.05). Control subjects, however, experienced no decline in these variables. In conclusion, the incidence of EIB in the figure skaters measured during this investigation (43 of 124 = 35%) is greater than that of the population at large and other highly trained athletes, signifying that screening for EIB and therapeutic follow-up are reasonable considerations for participants in this sport.